Time-sharing factors and their relation to cognitive abilities and personality traits - Jerneić, Željko (Array, 1994)
The aim of this research was (1) to analyze the factor structure of time-sharing performance and (2) to examine the relations of identified time-sharing factors to cognitive abilities and personality traits. Eight computerized choice-reactions and tracking tasks were performed both singly, one by one, and concurrently, in different dual-task combinations, by 98 female psychology students. The subjects also completed a series of paper-and-pencil tests comprising 6 cognitive ability measures (mainly from GATB) and 4 personality measures (from EPQ). A factor analysis of perceptual-motor performance identified three single-task and three time-sharing factors, supporting the notion of the process-specific time-sharing abilities. None of the factors correlated with the personality measures. Two of the time-sharing factors, however, correlated with primary mental abilities, in particular with perceptual speed and accuracy and numerical ability, rather than with measures related to reasoning ability. The findings suggest that speed of information processing may be a crucial factor in time-sharing performance.